2017
DOI: 10.1186/s13045-017-0404-4
|View full text |Cite
|
Sign up to set email alerts
|

High WT1 expression is an early predictor for relapse in patients with acute promyelocytic leukemia in first remission with negative PML-RARa after anthracycline-based chemotherapy: a single-center cohort study

Abstract: Wilms’ tumor gene 1 (WT1) expression is a well-known predictor for relapse in acute myeloid leukemia. We monitored WT1 decrement along the treatment course to identify its significant role as a marker for residual disease in acute promyelocytic leukemia (APL) and tried to suggest its significance for relapse prediction. In this single center retrospective study, we serially measured PML-RARa and WT1 expression from 117 APL patients at diagnosis, at post-induction and post-consolidation chemotherapies, and at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 8 publications
2
16
0
Order By: Relevance
“…Moreover, the expression increased during myelofibrotic transformation and high WT1 transcript levels could be linked to splenomegaly and thrombocytopenia and overexpression of WT1 was hypothesized to play an important role in the leukemic transformation of MPN [ 201 , 202 ]. Comparable with the results reported about WT1 expression in MPN, its expression is also higher in leukemia cells and LSCs compared to normal healthy hematopoietic cells and is a possible prognostic factor to predict clinical outcome and to detect MRD [ 203 , 204 , 205 , 206 ]. WT1 is a possible antigen to specifically target in leukemia patients as it was demonstrated that WT1-reactive cytotoxic T-cells mediate a strong anti-tumor immune response in post-transplant patients [ 207 ].…”
Section: Wt1-specific T-cellssupporting
confidence: 63%
“…Moreover, the expression increased during myelofibrotic transformation and high WT1 transcript levels could be linked to splenomegaly and thrombocytopenia and overexpression of WT1 was hypothesized to play an important role in the leukemic transformation of MPN [ 201 , 202 ]. Comparable with the results reported about WT1 expression in MPN, its expression is also higher in leukemia cells and LSCs compared to normal healthy hematopoietic cells and is a possible prognostic factor to predict clinical outcome and to detect MRD [ 203 , 204 , 205 , 206 ]. WT1 is a possible antigen to specifically target in leukemia patients as it was demonstrated that WT1-reactive cytotoxic T-cells mediate a strong anti-tumor immune response in post-transplant patients [ 207 ].…”
Section: Wt1-specific T-cellssupporting
confidence: 63%
“…Expression of WT1 on normal hematopoietic progenitor cells was reported as at least 10 times less than in AML cells, confirming the overexpression of the WT1 gene in leukemic cells [114]. Quantification of WT1 gene expression can be used to predict the probability of relapse and to detect minimal residual disease in AML patients [115,116]. Interestingly, WT1 was ranked as the top immunotherapy target in cancer by a national cancer institute pilot project for the prioritization of cancer antigens [117].…”
Section: Hla-dependent Antigensmentioning
confidence: 95%
“…Wilms’ tumor antigen 1 ( WT1 ) is more abundant in leukemic cells than in normal hematopoietic cells. Quantitative assessment of WT1 gene transcript abundance by real-time quantitative PCR (RQ-PCR) has been shown to be useful for predicting clinical outcome and prognosis in acute myelogenous leukemia (AML), and for detecting minimal residual disease (MRD) [13]. In addition, the expansion of WT1 -specific CD8 + T cells was correlated with graft-versus-leukemia (GVL) effect in 10 subjects with acute lymphoblastic leukemia [4].…”
mentioning
confidence: 99%